Bioactivity screening, extraction, and separation of lactate dehydrogenase inhibitors from Polygala tenuifolia Willd. based on a hyphenated strategy. Issue 6 (22nd February 2017) - Li, Sainan; Liu, Shu; Liu, Zhiqiang; Liu, Chunming; Song, Fengrui; Pi, Zifeng
Abstract : Stroke is the second leading cause of death worldwide. Lactate dehydrogenase inhibitors are currently widely used in the treatment of ischemic stroke, and natural products are considered promising sources of lactate dehydrogenase inhibitors. In this study, ultrafiltration liquid chromatography coupled with mass spectrometry was used for the screening and identification of lactate dehydrogenase inhibitors from Polygala tenuifolia . Furthermore, five lactate dehydrogenase inhibitors, sibiricose A5, 3, 6′‐di‐ O ‐sinapoyl‐sucrose, glomeratose A, tenuifoliside B, and tenuifoliside C, were selected as target lactate dehydrogenase inhibitors. In addition, the five target compounds with purities of 96.45, 97.65, 96.38, 94.34, and 93.29% were extracted and isolated using a new hyphenated strategy of microwave‐assisted extraction coupled with countercurrent chromatography with a two‐phase solvent system of n ‐hexane/ n ‐butanol/ethanol/water (5.321:1.00:1.664:6.647). The bioactivities of the isolated compounds were analyzed using PC12 cells and the 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide assay. The results also demonstrated that microwave‐assisted extraction coupled with countercurrent chromatography is an efficient method of isolating chemical constituents from medicinal herbs. Moreover, the research route consisting of activity screening, extraction, separation, and activity verification of the compounds has the advantages of being efficient, orientated, and objective.